Sintering effects on Sm3+-doped willemite glass-ceramics: structural, mechanical, and optical studies - Cheong, Wei Mun; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Loh, Zhi Wei (Elsevier B.V., 2025)
Willemite glass-ceramics are promising for optoelectronic applications due to their compatibility with rare-earth dopants and stability. The use of sustainable raw materials such as glass waste further enhances their appeal in green material development. In this study, Sm3+-doped willemite glass-ceramics were synthesized from zinc-borosilicate glass using the melt and fast-quenching technique, followed by sintering, with soda-lime-silica glass waste serving as a substitute raw material for SiO2. X-ray diffraction (XRD) demonstrated the development of α-Zn2SiO4 crystals above 800 °C. Energy-dispersive X-ray (EDX) analysis showed Sm concentrated in the glassy phase (4.65 wt%), with minimal incorporation in crystalline regions (∼0.25 wt%). Vickers hardness and fracture toughness reached maximum values of (5.61 ± 0.14) GPa and (2.91 ± 0.55) MPa∙m1/2 when the sample was sintered at 800 °C. The optical absorption edge moved from 241 nm to 252 nm, and the direct band gap narrowed from (5.023 ± 0.003) eV to (4.451 ± 0.003) eV. Additionally, the sample sintered at 800 °C exhibited a 60.9 % increase in photoluminescence intensity compared to the as-synthesized glass. CIE chromaticity coordinates around (0.57, 0.42) and a CCT range of 1740–1810 K confirmed warm reddish-orange emission. These results highlight the material's potential as a sustainable reddish-orange phosphor for optoelectronic applications.